Magic school eaudiobook Magic school. - Grey, Phoenix (Realm Between, 2020)
Adventure calls! Reality and fantasy finally collide when a new member joins Azure's party. A dangerous encounter with a mimic makes him think twice about touching large chests. And learning magic proves to be a bigger pain than he could have ever imagined.